La recopilación de recursos electrónicos en línea de alta calidad científica: una propuesta metodológica para Historia Moderna - Téllez Alarcia, Diego (Revista General de Información y Documentación, 2003)
The intention of this contribution is to carry out a brief review of the different systems of retrieval and compilation of high-quality online electronic resources available on the Net and to introduce the contribution made by the magazine, Tiempos Modernos in the field of Early Modern History. A general methodological proposal, exportable to other disciplines, is also outlined for this tool which, though humbler than the big search engines, directories, and analytical guides, proliferates in some institutional web pages without following any minimum norms for the standardization or description of the links contained.